The Phenomenon of the Arab Spring Political Crisis in the Middle East - Rodotul Janah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
This paper aims to examine the Arab Spring phenomenon in the Middle East and explain the triggering factors of conflict with the impact of the Arab Spring phenomenon that occurred in the Middle East, namely in the political crisis. Democracy is a freedom for the people to express opinions and directly elect government leaders. People in Arab and Middle Eastern countries believe that democracy is a way to prevent the appearance of authoritarian power in Middle Eastern countries.